Security as a campaign issue: programmatic mobilization in Burkina Faso's 2020 elections. Issue 8 (17th November 2022) - Saidou, Abdoul Karim; Bertrand, Eloïse
ABSTRACT: Despite recent research suggesting that African parties engage with substantive issues more than was previously thought, the nature of issue mobilization and the drivers of programmatic appeals on the continent remain under-explored. This article analyses how presidential candidates addressed the issue of security during the 2020 election campaign in Burkina Faso – a country faced by a growing armed insurgency since 2016 – in order to understand the nature of these substantive appeals. Based upon the analysis of candidates' manifestos, Facebook pages, media appearances, as well as direct observation of campaign meetings held in the thirteen regional capitals, we find that the crisis context favoured the mobilization of substantive issues related to security during the campaign. Furthermore, though all candidates addressed security in valence terms, opposition candidates also claimed controversial sub-issues in an attempt to use a broader range of campaign strategies than the incumbent. Finally, a specific question (whether to negotiate with armed groups or not) became a salient programmatic cleavage during the campaign, which can be explained by strategic choices made by opposition parties and the incumbent that contributed to the emergence of credible, coherent, and polarized policy options, providing real programmatic substance to the electoral campaign.